2017
DOI: 10.1038/srep45364
|View full text |Cite
|
Sign up to set email alerts
|

Paroxetine alleviates T lymphocyte activation and infiltration to joints of collagen-induced arthritis

Abstract: T cell infiltration to synovial tissue is an early pathogenic mechanism of rheumatoid arthritis (RA). In the present work, we reveal that G protein coupled receptor kinase 2 (GRK2) is abundantly expressed in T cells of collagen-induced arthritis (CIA). A GRK2 inhibitor, paroxetine protects the joints from inflammation and destruction, primarily through inhibition of both CD4+ helper T (Th) cell and CD8+ cytotoxic T (Tc) cell migration to synovial tissue. Meanwhile, paroxetine restores the balance of Th/Tc, eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 38 publications
(41 reference statements)
0
33
0
Order By: Relevance
“…Results of the in vivo experiments demonstrated that 3′‐SL modulated pannus formation (Figure E), which mainly contains extensive infiltrates of immune cells (T cells, macrophages, monocytes and FLS) and increased numbers of osteoclasts (Roberts et al ., ; Wang et al ., ). To further confirm activation of T cells, monocytes and of osteoclastogenesis by 3′‐SL, we evaluated inhibition by 3′‐SL of the regulation of pro‐inflammatory cytokine expression by inflammatory immune cells (T cells and monocytes) and the suppression of osteoclastogenesis.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Results of the in vivo experiments demonstrated that 3′‐SL modulated pannus formation (Figure E), which mainly contains extensive infiltrates of immune cells (T cells, macrophages, monocytes and FLS) and increased numbers of osteoclasts (Roberts et al ., ; Wang et al ., ). To further confirm activation of T cells, monocytes and of osteoclastogenesis by 3′‐SL, we evaluated inhibition by 3′‐SL of the regulation of pro‐inflammatory cytokine expression by inflammatory immune cells (T cells and monocytes) and the suppression of osteoclastogenesis.…”
Section: Resultsmentioning
confidence: 97%
“…Rheumatoid arthritis (RA) is an autoimmune and chronic inflammatory disease. Although RA pathogenesis is not fully elucidated, synovial hyperplasia, pannus formation, inflammation, infiltration of various inflammatory cells and cartilage destruction are known to be involved because of dysfunction of fibroblast‐like synoviocytes (FLS), T lymphocytes and other immune cells such as B cells, monocytes and neutrophils (Noss and Brenner, ; Shi and Pamer, ; Roberts et al ., ; Wang et al ., ). Especially, FLS from the intimal lining are considered major effectors of cartilage destruction in RA based on their ability to produce large amounts of degradative enzymes (Bartok and Firestein, ).…”
Section: Introductionmentioning
confidence: 97%
“…However, the Food and Drug Administration-approved SSRI paroxetine was identified using a high throughput aptamer displacement assay to bind directly to GRK2 to inhibit its ability to phosphorylate rhodopsin, tubulin and thyrotropin-releasing hormone receptor, while increasing βAR-stimulated cardiomyocyte (in vitro) and cardiac (in vivo) contractility 7 . Subsequently, paroxetine has been shown to reverse cardiac dysfunction induced by either ischemia 8 or high fat diet 18 , inhibit T cell activation 19 and decrease fibroblast cytokine production 20 . Despite the increasing use of paroxetine in studies in which its effects are attributed to inhibition of receptor desensitization processes classically engaged by GRK2, such as βarr recruitment and GPCR internalization, no studies have confirmed whether it actually attenuates these responses.…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al constructed a high-density haplotype map of SNP markers in soybean through SLAF-seq technology and 4 candidate genes were identified for resistance to Sclerotinia sclerotiorum [23]. Zhang et al performed a GWAS using SLAF-seq to detect the SNP markers that were associated with growth traits in Jinghai Yellow chicken hens [24]. Li et al developed a SLAF-seq approach to reveal the genetic differences among Landrace, Erhualian, and Meishan pigs [25].…”
Section: Introductionmentioning
confidence: 99%